2017
DOI: 10.2174/1874306401711010031
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Hypercapnic Patients with COPD and Obesity Hypoventilation Syndrome Treated with High Intensity Non Invasive Ventilation in the Daily Routine Care

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…This somewhat unexpected finding might be due to better health behaviours in subjects with diabetes and cancer survivors. Although our results may also be partly due to the lack of power or coincident results related to multiple statistical testing, they highlight the need for comprehensive care of patients treated with The subjects in this study were adherent to NIV, with a median of 6 h. Our results are in line with those of the study by Blankenburg et al, although the discontinuation percentages in subjects with COPD and OHS in our study were slightly lower [18]. Moreover, discontinuation was not associated with survival in the subjects in the current study, even though discontinuation has previously been shown to be associated with worse survival in subjects with OHS [25].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This somewhat unexpected finding might be due to better health behaviours in subjects with diabetes and cancer survivors. Although our results may also be partly due to the lack of power or coincident results related to multiple statistical testing, they highlight the need for comprehensive care of patients treated with The subjects in this study were adherent to NIV, with a median of 6 h. Our results are in line with those of the study by Blankenburg et al, although the discontinuation percentages in subjects with COPD and OHS in our study were slightly lower [18]. Moreover, discontinuation was not associated with survival in the subjects in the current study, even though discontinuation has previously been shown to be associated with worse survival in subjects with OHS [25].…”
Section: Discussionsupporting
confidence: 87%
“…was slightly better than that identified in a study by Blankenburg et al (3.9 yrs. ), while a relatively long survival of OHS subjects was found in both studies[ 18 ]. Subjects with other diagnoses showed very variable prognoses in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, several observational studies and uncontrolled trials indicated that LTMV has a positive effect on survival in patients with NMD [1016], OHS [10, 13, 1720] and CWD [1013, 2123] relative to historical controls.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 32 articles: 27 were single-arm case series ( 3 , 14 , 16 , 23 26 , 28 , 54 72 ), 2 were observational studies with a control group published in abstract form ( 29 , 73 ), and 3 were RCTs ( 11 , 19 , 21 ).…”
Section: Resultsmentioning
confidence: 99%